Approaches and methods for assessing quality of life : an application to Czech municipalities with extended jurisdiction - Hanousek, Jakub; Dlouhý, Martin, 1970-; Pekár, Juraj; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2026)
The goal of this doctoral thesis is to measure the objective dimension of quality of life in mu-nicipalities with extended jurisdiction in the Czech Republic. Quality of life is measured by five composite indicators. Composite indicators were calculated using two methods based on sev-eral socio-economic factors. The methods for calculating composite indicators are the weighted sum approach method and the “Benefit of the doubt”, which is based on linear programming. In the weighted sum method, the target population groups were distinguished by determining different weights for individual socio-economic factors. The thesis also analyzes the effect of living on the Czech Republic state border on the quality of life, and individual neighboring countries are distinguished. Composite indicators are further analyzed by regression analysis with qualitative variables. The statistically significant results show that municipalities located near the border with Slovakia achieve average higher values of all five composite indicators than other municipalities. The results were further analyzed by spatial analysis. Positive spatial autocorrelation and so-called coldspots and hotspots were found. Hotspots were detected in municipalities with extended coverage bordering Slovakia, with some reaching inland. After including the spatial component in the regression model, the effect of the state border weakened. This is due to the fact that individual cold spots and hotspots have a significant inland extension from the border. The thesis also focuses on the political impact of the quality of life. The gains of selected political parties in the 2021 parliamentary elections in municipalities with extended jurisdiction are analyzed and further analyzed with the quality of life in these municipalities.
Vedoucí práce: Martin Dlouhý
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor disert. práce]; disertace; dissertations